The Impact of Minimum Gift Requirement and Number of Fundraising Staff on University Athletics Donors - Popp, Nels; Kavanagh, Ashley; Jensen, Jonathan A. (Journal of Intercollegiate Sport, 2022)
Many prior studies examining fundraising within university athletics programs have explored the effect of donor motivations and athletic success on giving, but the current study is the first to examine the impact of price setting and staffing (two factors under the control of athletics administrators) on number of donors. The purpose of the current study was to examine the relationship between (a) minimum gift price point and (b) total number of fundraising personnel, on the total number of donors at the lowest reward tier within NCAA Division I athletics departments. The research team used hierarchical regression to develop four models to examine the relationships between key variables and total number of donors. Independent variables utilized included university conference affiliation, institutional factors, athletic success factors, and the variables of interest, which were minimum gift amount required to join the donor program and the total number of fundraising staff. The dependent variable examined was total number of donors at the lower reward tier. The final model explained 73.1% of the variance in number of donors. The variables of interest (minimum price point and total number of staff) explained 20.8% of the variance when controlling for key factors such as athletic success and conference affiliation.